Synthesis of Li2S-Carbon Cathode Materials via Carbothermic Reduction of Li2SO4 - Shi, Jiayan; Zhang, Jian; Zhao, Yifan; Yan, Zheng; Hart, Noam; Guo, Juchen (Frontiers in Energy Research, 2019)
Pre-lithiated sulfur materials are promising cathode for lithium-sulfur batteries. The synthesis of lithium sulfide-carbon (Li2S-C) composite by carbothermic reduction of lithium sulfate (Li2SO4) is investigated in this study. The relationship between reaction temperature and the consumption of carbon in the carbothermic reduction of Li2SO4 is first investigated to precisely control the carbon content in the resultant Li2S-C composites. To understand the relationship between the material structure and the electrochemical properties, Li2S-C composites with the same carbon content are subsequently synthesized by controlling the mass ratio of Li2SO4/carbon and the reaction temperature. Systematic electrochemical analyses and microscopic characterizations demonstrate that the size of the Li2S particles dispersed in the carbon matrix is the key parameter determining the electrochemical performance. A reversible capacity of 600 mAh g−1 is achieved under lean electrolyte condition with high Li2S areal loading.